Microwave Assisted Synthesis of Substituted Coumarinyl Chalcones as Reaction Intermediates for Biologically Important Coumarinyl Heterocycles - JAYASHREE, B.S.; ARORA, SAMEER; VENUGOPALA, K.N. (Asian Journal of Chemistry, 2010)
Some of the 5(substituted and unsubstituted phenyl)-1- phenyl-2-pyrazoline-3''-yl-6-chloro coumarins were synthesized by the reaction between 3-(3-substituted benzylidine) acetyl 6- chloro coumarin and phenyl hydrazine in presence of pyridine. The former was obtained by treating 3-acetyl-6-chloro coumarin and 3,4,5-trimethyl benzaldehyde. Microwave technology was used at this stage to reduce the reaction time and improve the yield of the product. The resulting compounds were characterized by spectral data and few of the compounds were determined for their partition coefficient and in vitro antioxidant properties by DPPH* method. One of the synthesized compounds was found to be a potential candidate for scavenging radical oxygen.